Natural organohalogens in sediments - Müller, German; Nkusi, Gérard; Schöler, Heinz Friedrich (Journal für praktische Chemie, 1996)
Recent fluvial, lacustrine and marine sediments were found to contain significant concentrations of organohalogens which cannot be explained by known anthropogenic halogen compounds. The assumption of a natural source for the major part of these organohalogens is strongly supported by the fact that in lacustrine sediments deposited some hundred years ago - where no industrial chlorinated organic compounds should be expected - concentrations between 30 and 100 mg/kg of adsorbable organic halogens (AOX, expressed as equivalent chlorine) were detected. In anoxic sapropels of the Black Sea, several thousand years old and having a high organic content (mainly derived from marine phytoplankton), organic bromine and iodine occur at levels up to 313 and 465 mg/kg, respectively. AOX concentrations in biogenic sediments from various epochs and representing different stages of coalification (peat - lignite - bituminous coal - anthracite) are clear evidence for naturally occurring organohalogens. Plant material has therefore to be considered as the most important primary source of high molecular weight organohalogens in sediments. In addition, natural low molecular organohalogens produced by bacteria, fungi, algae (such as haloalkanes, terpenes, amino acids and peptides, chlorophenols etc.) will also accumulate in the sediment and become part of its primary organohalogen content. As a secondary source of organohalogens in sediments their formation in the sediment itself has to be considered. Biotic halogenation of organic substrates by haloperoxidases (to occur in algae and other marine organisms but also in terrestrial lichens and fungi) leading to volatile organohalogens has been observed already. Only little knowledge exists on abiotic halogenation. In preliminary investigations in the system trichloroacetic acid - water - humic substances, chlorinated compounds could be identified. A transfer of (low molecular) organohalogens from the sediment into the interstitial water is obvious: If compared with the supernatant lake water, AOX concentrations in interstitial water of Lake Constance sediments are enriched by a factor of 20-70. Under anaerobic conditions bacterial decomposition of organohalogens leads to the release of halide ions into the interstitial water of the sediment. The results presented here fully confirm our previous conclusion [1], that the AOX value cannot be used exclusively as a sum parameter for anthropogenic organic halogen compounds.